Secondary Stroke Prevention in Nonvalvular Atrial Fibrillation. Issue 11 (November 2016) - Damani, Rahul H.; Suarez, Jose I.
Abstract : Abstract: Approximately 750, 000 US adults per year experience a stroke. On average, the annual risk for future ischemic stroke (secondary stroke) after an initial ischemic stroke or transient ischemic attack is approximately 3% to 4%. Cardioembolic strokes account for 20% to 25% of all strokes, with nonvalvular atrial fibrillation (NVAF) considered one of the main sources of embolism; this explains up to half of all cardioembolic strokes. We present the risk factors for stroke in NVAF, risk stratification, a diagnosis of NVAF, and treatment and prevention of stroke in NVAF. We reviewed the literature by performing a PubMed search of articles focusing on secondary stroke prevention in NVAF. This review examines the findings of major clinical trials and society guidelines for secondary stroke prevention in NVAF and presents a cost-effectiveness analysis. Abstract : Stroke is a leading cause of morbidity in the United States, with approximately 750, 000 adultsper year experiencing a stroke. This review focuses on secondary stroke prevention from nonvalvular atrial fibrillation (NVAF), which accounts for a majority of cardioembolic strokes. As such, stroke prevention in atrial fibrillation represents a major public health concern, with a significant impact on healthcare costs. This review identifies risk factors of stroke in nonvalvular atrial fibrillation and assists clinicians with risk stratification and appropriate therapies using evidence in the literature and a cost-effectiveness analysis.